What not to wear for every occasion. - Woodall, Trinny; Constantine, Susannah (Weidenfeld & Nicolson, 2003)
In What Not to Wear we established the rules for dressing to suit your body shape. While you now know which skirt to avoid and which dress length to wear, many women say they still don't know what to wear to certain occasions - a job interview, a hot date, a wedding, a school function, going on from work, or just running around. This book is occasion led. It brings together those other elements that will give you total confidence to attend any event, work in any environment, go anywhere on holiday, and feel totally appropriately dressed, FOR YOU. Whether you want your look to be casual, trendy or smart, Susannah and Trinny will show you how to sally forth with style and confidence. --Publisher's description.